Least Squares Estimation and Fuzzy Logic Based Condition Monitoring for High Redundancy Actuator. Issue 1 (July 2017) - Antong, Hasmawati; Dixon, Roger; Ward, Christopher P.
Abstract: The high redundancy actuator concept that is inspired by biomimetics is an approach to fault tolerant actuator that aims to provide fault tolerance using relatively large number of actuation elements. The actuation elements are assembled in parallel and series configuration to form a single actuator that has intrinsic fault tolerance. During normal operations, it is possible that some of these elements are operational and some are faulty. As one or more of the actuation elements fail, the actuator capability will fall below that required by the application. Therefore, it is essential to have a condition monitoring algorithm to detect early signs of deterioration so that maintenance activity can be planned to avoid failure and to reduce down time and maintenance costs. This paper discusses the condition monitoring algorithm which is based on least squares parameter estimation and fuzzy logic to give indication of either the actuator is still in healthy condition or some elements are started to fail.